Indonesian Favorite Destinations: Antecedent and Consequence Destination Experience - Nuryanti Taufik; Faizal Haris Eko Prabowo (Universitas Airlangga, 2020)
Almost all countries in the world try to increase the attractiveness of tourist destinations owned by their countries, including Indonesia. Various strategies have been decided by the stakeholders in the tourism industry to lure tourists to their tourist destinations. The purpose of this study is to develop a model in the tourism industry by analyzing tourist behavior in returning visits to a tourist destination. This study uses a survey method with a quantitative approach. The attitude measurement scale is the differential magnetic scale, the primary data obtained from 502 respondents who had visited Bandung, or Yogyakarta, or Bali. The analytical tool used in this study is Structure Equation Modeling with AMOS 23.0 software. There are six variables examined in this study, namely revisit intention, e-WOM, destination experience, destination identity, destination service quality, and destination natural quality. The results found that revisit intention and e-WOM will be affected by destination experience. A pleasant experience during a visit to a tourist destination can be maintained by the right destination identity and destination service quality. Also, destination experience strengthened by excellent destination natural quality. This research model can be adopted in various tourist destinations to increase the number of tourists visiting.